The correct answers are:
(1) (Option B) -1299
(2) (Option A) -2
(3) (Option A) b < 13
(4) (Option D) m = 5
(5) (Option D) 6
(6) (Option B) 2
(7) (Option A) p > 11
(8) (Option B) x = 6
(9) (Option A) h < –9
(10) (Option B) C = D ÷ AB
(11) (Option B) y = –45
(12) (Option A) y = 11
(13) (Option D) q = 13
(14) (Option A) M = K/LN
(15) (Option C) h = 63
(16) (Option C) –3p + 11
(17) (Option C) ![10\frac{1}{4}](https://tex.z-dn.net/?f=10%5Cfrac%7B1%7D%7B4%7D%20%20%20)
(18) (Option D) y = 31
(19) (Option D) R = E ÷ I
(20) (Option B) y = 4
Explanations:
(1) The Given Expression:
-282 - (+1017)
= -282 - 1017
= -1299 (Option B)
(2) The total balance = $35
One check = $10
Three checks = 3 * $9 = $27
Balance now = Total balance - One check + Three check = $35 - $10 - $27 = -2 (Option A)
(3) The given expression:
3b – 7 < 32
Add 7 on both sides:
3b -7 + 7 < 32 + 7
3b < 39
Divide by 3 on both sides:
![\frac{3b}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3b%7D%7B3%7D%20%3C%5Cfrac%7B39%7D%7B3%7D%20%20%20%20)
b < 13 (Option A)
(4) The given expression:
4m + 9 + 5m – 12 = 42
9m = 42 + 12 - 9
9m = 45
Divide both sides with 9:
![\frac{9m}{9} =\frac{45}{9} \\ m=5](https://tex.z-dn.net/?f=%20%5Cfrac%7B9m%7D%7B9%7D%20%3D%5Cfrac%7B45%7D%7B9%7D%20%20%5C%5C%20m%3D5%20)
The correct answer is m=5 (Option D)
(5) The given expression:
13 + (–12) – (–5)
= 13 - 12 + 5
= 6 (Option D)
(6) Mathematically, we can write "four times a number plus 3 is 11" as:
4x + 3 = 11
Where,
x = The number we require
4x = 11 - 3
4x = 8
x = 2 (Option B)
(7) The given expression:
12p + 7 > 139
Subtract 7 on both sides:
12p + 7 - 7 > 139 -7
12p > 132
Divide 12 on both sides:
![\frac{12p}{12} >\frac{132}{12}](https://tex.z-dn.net/?f=%20%5Cfrac%7B12p%7D%7B12%7D%20%3E%5Cfrac%7B132%7D%7B12%7D%20%20%20%20)
p > 11 (Option A)
(8) The given equation:
7x = 42
Divide the equation with 7 on both sides:
![\frac{7x}{7} =\frac{42}{7}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7x%7D%7B7%7D%20%3D%5Cfrac%7B42%7D%7B7%7D%20%20%20%20)
x = 6 (Option B)
(9) The given expression:
9h + 2 < –79
Subtract 2 on both sides:
9h + 2 - 2 < -79 - 2
9h < -81
h < -9 (Option A)
(10) The given equation:
D = ABC
Now divide both sides with AB on both sides:
![\frac{D}{AB} =\frac{ABC}{AB} \\ C =\frac{D}{AB}](https://tex.z-dn.net/?f=%20%5Cfrac%7BD%7D%7BAB%7D%20%3D%5Cfrac%7BABC%7D%7BAB%7D%20%5C%5C%20C%20%3D%5Cfrac%7BD%7D%7BAB%7D%20%20%20%20%20%20)
Hence C = D ÷ AB (Option B)
(11) Given equation:
![\frac{y}{9} + 5 = 0](https://tex.z-dn.net/?f=%20%5Cfrac%7By%7D%7B9%7D%20%2B%205%20%3D%200%20%20)
Subtract 5 on both sides:
![\frac{y}{9} +5 -5 = 0 -5](https://tex.z-dn.net/?f=%20%5Cfrac%7By%7D%7B9%7D%20%2B5%20-5%20%3D%200%20-5%20)
y = -5*9 = -45
y = -45 (Option B)
(12) Given equation:
12y = 132
Divide both sides by 12:
![\frac{12y}{12} =\frac{132}{12}](https://tex.z-dn.net/?f=%20%5Cfrac%7B12y%7D%7B12%7D%20%3D%5Cfrac%7B132%7D%7B12%7D%20%20%20%20)
y = 11 (Option A)
(13) The given equation:
3q + 5 + 2q – 5 = 65
5q = 65
Divide both sides with 5 and simplify:
q = 13 (Option D)
(14) Given formula:
K = LMN
To find M, divide both sides with LN:
![\frac{K}{LN} =\frac{LMN}{LN} \\ M = \frac{K}{LN}](https://tex.z-dn.net/?f=%20%5Cfrac%7BK%7D%7BLN%7D%20%3D%5Cfrac%7BLMN%7D%7BLN%7D%20%5C%5C%20%20M%20%3D%20%5Cfrac%7BK%7D%7BLN%7D%20%20)
Hence the correct answer is
(Option A)
(15) Given formula:
h/9 = 7
Multiply both sides with 9:
h = 7 * 9
h = 63 (Option C)
(16) Given expression:
4p + 9 + (-7p) + 2
4p + 9 -7p +2
-3p + 11 (Option C)
(17) The given formula:
16y = 164
Divide both sides with 16:
![\frac{16y}{16} =\frac{164}{16} \\ y = 10\frac{1}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B16y%7D%7B16%7D%20%3D%5Cfrac%7B164%7D%7B16%7D%20%5C%5C%20y%20%3D%2010%5Cfrac%7B1%7D%7B4%7D%20%20%20)
Hence the correct answer is (Option C) ![y = 10\frac{1}{4}](https://tex.z-dn.net/?f=y%20%3D%2010%5Cfrac%7B1%7D%7B4%7D%20%20%20)
(18) Given equation:
4y + 228 = 352
Subtract both sides with 228:
4y + 228 - 228 = 352 - 228
4y = 124
Divide both sides by 4 and simplify:
y = 31 (Option D)
(19) The given formula:
E = IR
To find R, divide both sides with I:
R = E ÷ I (Option D)
(20) Given equation:
6y - 20 = 2y - 4
=> 6y - 2y = -4 + 20
=> 4y = 16
Divide both sides with 4 and simplify:
y = 4 (Option B)